2016
DOI: 10.1155/2016/6268938
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Detection and Annual Extreme Temperature Analysis of the Amur River Basin

Abstract: This paper aims to detect climate change points and compare the extreme temperature changes with the average-value changes in the Amur River basin. The daily air temperatures of 44 stations in the Amur River basin were collected from April 1, 1954, to March 31, 2013. The change points for annual mean and extreme temperature in 44 individual stations and their average were detected by the Mann-Kendall test, respectively. The annual mean temperature changed during 1980s in terms of increased mean value and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…As the tenth largest river basin in the world, the natural conditions of the Amur River Basin (ARB), a transboundary basin in eastern Eurasia, vary greatly from region to region. In addition, the impact intensity of human activities on the ground vegetation has varied considerably under the influence of different national policies, lifestyles, and economic development [34][35][36][37][38]. In recent decades, significant climate changes have been observed in the ARB, where an annual mean temperature warming rate of about 0.34 °C/10a for 1975-2004 was reported, which is approximately 2.5 times higher than that for the 1891-2004 period [39].…”
Section: Introductionmentioning
confidence: 99%
“…As the tenth largest river basin in the world, the natural conditions of the Amur River Basin (ARB), a transboundary basin in eastern Eurasia, vary greatly from region to region. In addition, the impact intensity of human activities on the ground vegetation has varied considerably under the influence of different national policies, lifestyles, and economic development [34][35][36][37][38]. In recent decades, significant climate changes have been observed in the ARB, where an annual mean temperature warming rate of about 0.34 °C/10a for 1975-2004 was reported, which is approximately 2.5 times higher than that for the 1891-2004 period [39].…”
Section: Introductionmentioning
confidence: 99%
“…The key to this study was identifying the different magnitudes and directions of the impacts of climate variability and land-use changes on the hydrological variables over the last several decades and further assessing the relationships between the individual climatic factors/land-use types and the hydrologic components. To identify the variations in the impacts, the authors divided the simulation periods according to the historical land-use changes reported in the literature mentioned in the study area section [17,18,24,27,29,49] and the characteristic analytical results of the climate and land-use changes.…”
Section: Simulation Period Divisionmentioning
confidence: 99%
“…As the 10th largest river basin in the world and the largest in the Russian Far East, the Amur River Basin (ARB) is one of the most vulnerable areas to climate change and human activities in the world [17]. In recent decades, the annual average maximum temperature, minimum temperature, mean temperature, and annual precipitation in the ARB have exhibited generally increasing trends [18][19][20][21]. Moreover, significant regional, seasonal, and interannual variations in temperature and precipitation have been investigated in portions of the ARB [1,7,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many heat-related deaths occurred during the heat wave events in Chicago in 1995, in Western Europe in 2003, and in East Asia in 1994 [6][7][8]. Also, recent studies revealed significant worldwide warming and a general increase in the frequency and persistence of extreme temperature and precipitation events (e.g., [9][10][11][12][13]). So far, extensive researches have been conducted to detect the effects of climate change on climatic variables at a regional scale.…”
Section: Introductionmentioning
confidence: 99%